Menakar Eksistensi Negara Multi Etnik Modern - Zainuri, Achmad (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
The failure of politics and political study to contribute to the appropriate format impacts any terrible in life. Any conflicts, violences, and even war are recognized as the failure of politics. There for the growth of true politicalsystems is to reform the political life.Â